2013
DOI: 10.1371/journal.pone.0073370
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Excitatory Drive to Spinal Gabaergic Neurons of Neuropathic Mice

Abstract: Adequate pain sensitivity requires a delicate balance between excitation and inhibition in the dorsal horn of the spinal cord. This balance is severely impaired in neuropathy leading to enhanced pain sensations (hyperalgesia). The underlying mechanisms remain elusive. Here we explored the hypothesis that the excitatory drive to spinal GABAergic neurons might be impaired in neuropathic animals. Transgenic adult mice expressing EGFP under the promoter for GAD67 underwent either chronic constriction injury of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 56 publications
1
39
1
Order By: Relevance
“…I H , particularly HCN4, is also found in a subpopulation of tonic firing neurons in lamina II of the spinal dorsal horn (Grudt and Perl, ; Hughes et al., , ). Although HCN4 is susceptible to ivabradine block (Bucchi et al., ), a tonic firing phenotype is often observed in inhibitory interneurons (Yasaka et al., ; Hughes et al., , ; Leitner et al., ). Actions of ivabradine are thus unlikely to reflect HCN4 blockade in these tonic firing inhibitory interneurons as this would be expected to decrease their firing rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I H , particularly HCN4, is also found in a subpopulation of tonic firing neurons in lamina II of the spinal dorsal horn (Grudt and Perl, ; Hughes et al., , ). Although HCN4 is susceptible to ivabradine block (Bucchi et al., ), a tonic firing phenotype is often observed in inhibitory interneurons (Yasaka et al., ; Hughes et al., , ; Leitner et al., ). Actions of ivabradine are thus unlikely to reflect HCN4 blockade in these tonic firing inhibitory interneurons as this would be expected to decrease their firing rate.…”
Section: Discussionmentioning
confidence: 99%
“…IH, particularly HCN4, is also found in a subpopulation of tonic firing neurons in lamina II of the spinal dorsal horn (Grudt and Perl, 2002;Hughes et al, 2012Hughes et al, , 2013. Although HCN4 is susceptible to ivabradine block (Bucchi et al, 2006), a tonic firing phenotype is often observed in inhibitory interneurons (Yasaka et al, 2010;Hughes et al, 2012Hughes et al, , 2013Leitner (Bennett and Xie, 1988) received two doses per day of 6 mg/kg ivabradine via gastric gavage. Withdrawal threshold was determined with von Frey filaments and the data were plotted with the blue symbols (•).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to changes in chloride gradient (Coull et al, 2003(Coull et al, , 2005 and decreased excitatory drive to inhibitory neurons (Balasubramanyan et al, 2006;Lu et al, 2009;Leitner et al, 2013), this may involve a loss of GABAergic terminals (Lorenzo et al, 2014) or reduced glycine release (Imlach et al, 2016). Tactile and innocuous information is carried by Ab fibers, which synapse primarily onto dorsal horn neurons in laminae III and IV (Abraira et al, 2017), whereas noxious information carried by C and Ad fibers is transmitted to the superficial laminae I and II (Peirs and Seal, 2016) (Fig.…”
Section: Altered Sensory Processing and Generation Of Allodyniamentioning
confidence: 99%
“…We hypothesize that IL-1β released from microglia or astrocytes rapidly potentiates glycinergic synapses on GABAergic lamina II interneurons that normally inhibit the passage of nociceptive signals to the brain; after inflammation, the nociception-transmitting neurons will in turn be rapidly disinhibited via this mechanism, enhancing the perceived pain and contributing to hyperalgesia and allodynia (44). GlyR LTP may operate in tandem with LTP at excitatory primary afferent synapses, causing disinhibition and opening the "gate" to enhanced pain signaling, both by unmasking A-fiber inputs onto lamina I and III projection neurons (21), and reducing the excitatory drive to GABAergic lamina II neurons (69). The dorsal horn circuit is complex, and more work will be required to fully understand the role of GlyR LTP in nociception; in particular, we need to determine which other dorsal horn neurons can also undergo GlyR LTP.…”
Section: Glycine Receptor Trafficking and Channel Properties Modulatementioning
confidence: 99%